The importance of cytoplasmic strings during early human embryonic development - Joo, Kata; Nemes, Annamaria; Dudas, Beata; Berkes-Bara, Eva; Murber, Akos; Urbancsek, Janos; Fancsovits, Peter (Frontiers in Cell and Developmental Biology, 2023)
Objectives: During human in vitro fertilisation (IVF) treatments, embryologists attempt to select the most viable embryos for embryo transfer (ET). Previously, embryos were evaluated based on light microscopic morphological parameters. However, this is currently accomplished by morphokinetic analysis of time-lapse recordings. This technique provides us the opportunity to observe cytoplasmic strings at the blastocyst stage. The aim of this work was to examine the relationship between the presence of cytoplasmic strings (CS) and the embryo viability in human in vitro fertilised embryos. Study design: Herein, we present an evaluation of the morphokinetic data on the development of embryos obtained during IVF treatments performed at the Division of Assisted Reproduction between December 2020 and March 2021. The dynamics of embryo development, embryo morphology, and morphokinetic scores generated by a time-lapse system were compared between the presence of cytoplasmic strings (CS+) and their absence (CS-) at the blastocyst stage. Results: The development of 208 embryos from 78 patients was examined. Moreover, 81.2% of the embryos had CS in the blastocyst stage; 77% of CS existed in embryos created by conventional IVF, while 86% of CS existed in embryos fertilised by intracytoplasmic sperm injection (ICSI) (p = 0.08). A greater number of CS+ embryos developed into a higher quality blastocyst (52.1% vs. 20.5%, p = 0.02). The morphokinetic score values characterising the development of embryos, such as Known Implantation Data Score (KIDScore) and Intelligent Data Analysis (iDAScore), were higher in CS+ groups (KID: 6.1 ± 2.1 vs. 4.7 ± 2.07; iDA: 8.0 ± 1.9 vs. 6.8 ± 2.3, p < 0.01). The dynamics of the early embryo development were similar between the two groups; however, CS+ embryos reached the blastocyst stage significantly earlier (tB: 103.9 h vs. tB: 107.6 h; p = 0.001). Conclusion: Based on our results, the number of embryos with cytoplasmic strings was higher than that without cytoplasmic strings, and its presence is not related to the fertilisation method. These embryos reached the blastocyst stage earlier, and their morphokinetic (KIDScore and iDAScore) parameters were better. All these results suggest that the presence of CS indicates higher embryo viability. The examination of this feature may help us make decisions about the embryos with higher implantation potential.